Misunderstanding Metatheorizing. (29th July 2013) - Edwards, Mark G.
<x xml:space="preserve">Abstract</x> Metatheorizing is an important but generally poorly understood genre of social science inquiry that has particular relevance to systems research. In this paper, I define and present the major characteristics of metatheoretical research, discuss why it is neglected as a form of research and how it is often misunderstood and inadequately represented in the systems and management science literature. I illustrate the discussion with some examples of misunderstanding of metatheorizing from the systems science literature. I also make some recommendations for how researchers can improve their own metatheorizing and so, hopefully, help this important form of research become more widely acknowledged and critically appreciated. Copyright © 2013 John Wiley & Sons, Ltd.